2017
DOI: 10.1002/qj.3127
|View full text |Cite
|
Sign up to set email alerts
|

A long‐lived supercell over mountainous terrain

Abstract: The life cycle of a convective storm forming over highly complex topography on the northern side of the Alps is studied. Moist convection began ahead of a cold front in the late morning of 2 August 2007 in eastern Switzerland. It developed into a supercell storm that moved along the Alpine main crest for more than 8 h, passed over several 2000 m high ridges and ultimately dissipated over eastern Austria. This study analyzes the impact of topography on the pre‐storm environment and on the storm development usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 58 publications
1
10
0
Order By: Relevance
“…Some supercells that survived into the lee exhibited a brief enhancement in low-level rotation if they propagated over a cyclonic lee vortex. Other studies of mountain convection have found that enhanced lee-side vertical shear, owing to thermally induced plain-to-mountain flow, can promote supercell formation and/or maintenance [64,65].…”
Section: Orographic Impacts On Supercell Storm Environmentsmentioning
confidence: 95%
“…Some supercells that survived into the lee exhibited a brief enhancement in low-level rotation if they propagated over a cyclonic lee vortex. Other studies of mountain convection have found that enhanced lee-side vertical shear, owing to thermally induced plain-to-mountain flow, can promote supercell formation and/or maintenance [64,65].…”
Section: Orographic Impacts On Supercell Storm Environmentsmentioning
confidence: 95%
“…Supercells are the most intense storms in the spectrum of thunderstorms and have produced some of the largest short‐term rainfall rates in the United States (Bunkers & Doswell, ; Doswell et al, ; Giordano & Fritsch, ; Nielsen et al, ; Rogash & Racy, ; Smith et al, ). Recent studies are shedding light on both the dynamics and climatology of supercells in mountainous terrain (see, e.g., Bosart et al, ; Markowski & Dotzek, ; Scheffknecht et al, ).…”
Section: The Strangest Floods: the Blue Mountains Of Eastern Oregonmentioning
confidence: 99%
“…Eyewitness accounts of the storm suggest that it may have been a supercell thunderstorm, with one observer describing the storm as "a broad black streak almost straight north of us which seemed to be coming straight down from the sky" (Byrd, 2009). Supercells are the most intense storms in the spectrum of thunderstorms and have produced some of the largest short-term rainfall rates in the United States (Bunkers & Doswell, 2016;Doswell et al, 1996;Giordano & Fritsch, 1991 and climatology of supercells in mountainous terrain (see, e.g., Bosart et al, 2006;Markowski & Dotzek, 2011;Scheffknecht et al, 2017).…”
Section: Water Resources Researchmentioning
confidence: 99%
“…In combination with horizontal advection towards mountainous regions, elevated stable layers may thus favour the accumulation of moist static energy within valleys and the establishment of convectively or potentially unstable conditions. Furthermore, wind shear across stable layers might aid convective organization and enhance storm longevity [215].…”
Section: Multiscale Interactionsmentioning
confidence: 99%